Investigation of the geomagnetic storms’ impact on low-latitude ionosphere: case studies of October 2003 and March 2015 events - Hammed Adeniyi Lawal; Isreal Leke Elijah; Edwin Beshel Ayabie; Yusuf Bello; Joseph Alao; Innocent Davidson (Proceedings of the Nigerian Society of Physical Sciences)
Geomagnetic storms can significantly impact the Earth's upper atmosphere known as the ionosphere used for communication and navigation, particularly at low latitudes. This study examines the effects of two major geomagnetic storms on the low-latitude ionosphere that occurred during October 2003 and March 2015. In the analysis of the two events, data from NASA Space Physics data resources, Omni web, were analysed. Our analysis of the electron density, temperature, and ion composition data reveals significant disturbances in the ionosphere during both storms. The October 2003 storm caused a decrease in electron density and an increase in temperature, while the March 2015 storm had a more moderate impact. Our results highlight the importance of understanding geomagnetic storms' effects on the low-latitude ionosphere, particularly for mitigating their impacts on radio communication, navigation, and satellite operations. This study contributes to our understanding of geomagnetic storms' effects on the ionosphere and provides valuable insights for future research and applications.